The Media Framing of India’s Nuclear Weapons Discourse - Sitakanta Mishra; Hely Desai (International Journal of Nuclear Security, 2025)
The Indian media has had an immense role in framing public perceptions of nuclear weapons within the Indian subcontinent. Examining the largely nationalistic tone of news coverage helps analyze how the media has shaped India’s idea of its status as a nuclear weapon state. Examining the sociocultural discourse around the bomb, this paper analyzes the major influence that the Indian media has in information distribution and how that influence translates to the formation of the atomic attitudes of the masses. In situating the Indian media’s approach to nuclear weapons at large, this work studied the framing of domestic nuclear weapons discourse in Indian English-language newspapers. The research also articulated the nuclear takes on iconic daily comic strips, which play an important role in gauging the moods and anxieties of the masses, or the common man, as it happened. Sidelining the technical understanding of nuclear weapons from a scientific perspective, this paper incorporates a cultural and sociopolitical understanding of the nuclear weapons policy of India by further examining the media portrayal of the nuclear weapons debate beyond print media and into 24/7 news channels, social media, and entertainment mediums, such as movies and television shows. This study concluded that the media framing of India’s nuclear weapons policy is one-sided and mostly nationalistic; the opposition to the nuclear weapons program is nonexistent or meager. This paper also prescribes that the media has to play a more constructive role in educating the public because the focus of domestic debate has moved now from weapons issues to nuclear energy and safety and security.
Keywords: Nuclear weapons; role of media; nuclear proliferation; party politics; domestic nuclear debate; public perception